Cartoons in Symbolic Representations of Silent Connivance among Nigerian Stakeholders in Increasing Insecurity: Multimodal Analysis - Ifeyinwa Chukwuokoro (PhD), (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Insecurity is a monster that has clutched Nigeria, with its venom posing serious challenges. It has physical and political perspectives, and gets continually constructed, recreated, and reproduced in complicity and silence. This paper offers a multimodal discourse analysis of political cartoons as an attempt to study the construction and projection of silent connivance by social actors in insecurity discourse in Nigeria. It adopts Kress and van Leeuwen’s model of Visual Grammar, and examines three online editorial cartoons published in 2022. Descriptive survey, content analysis and interpretative techniques are employed in the analysis. The analysis reveals the government and its agents as participants that connive with insecurity initiators to perpetrate crimes against the vulnerable masses. In doing so, silent connivance strategies are deployed by government and its agents for active suppression of insecurity reportage. It also unveils the roles of visual and linguistic resources in constructing and depicting silent strategies of complicities of major social actors in insecurity contexts in Nigeria. Journalists, online influencers and socio-political activists are represented as dogs lured to lose strength in their acting capabilities to quit their watchdog duties. The study concludes that silence serves as a strategic mechanism for amplifying violence by politicians and their allies. It recommends pragmatic media freedom, practice of ethical reportage, and deconstruction of silent connivance in insecurity contexts as the panacea.
Keywords: Insecurity; Silent Connivance; Political Cartoons; Visual Grammar; Media Freedom